Inovasi Media, Sumber Belajar, dan Alat Peraga Pembelajaran SKI MI-MTs - nisrina; Muhamad Syaifudin Ahyar; Badrus Zaman (PERMAI: Jurnal Pendidikan dan Literasi Madrasah Ibtida'iyah, 2026)
Innovation in learning media, learning resources, and teaching aids plays a crucial role in improving the quality of Islamic Cultural History (Sejarah Kebudayaan Islam/SKI) learning at Madrasah Ibtidaiyah (MI) and Madrasah Tsanawiyah (MTs). This study aims to analyze concepts and forms of innovation in media, learning resources, and teaching aids used in SKI learning and their contribution to creating effective and meaningful learning experiences. This research employed a library research method by examining relevant books and scientific journals related to educational innovation and SKI learning. The findings indicate that the integration of various media, diverse learning resources, and contextual teaching aids can enhance students’ understanding, learning motivation, and appreciation of Islamic historical values. Therefore, innovation in SKI learning is essential to support contextual, interactive, and value-based education in the digital era.